The Role of the Land and Building Tax Collection System in Optimizing the Achievement of Original Income Target in Tanjung Anom Village - Tanjung, Endah Suharlin; Gultom, Eva Ulina; Arnita, Vina (International Journal of Integrative Sciences, 2024)
This study aims to analyze the implementation of the Rural Land and Building Tax (PBB-P2) collection system in Tanjung Anom Village, Pancur Batu District, Deli Serdang Regency. This study was conducted with a qualitative approach, using data collection methods through observation, interviews, and documentation. The data collected includes the process of registration, determination, payment, billing, and supervision of PBB-P2 receipts. The results of the study indicate that the implementation of the PBB-P2 collection system in Tanjung Anom Village has been running in accordance with the established Standard Operating Procedure (SOP). The process includes registration of tax objects, determination of Taxable Object Sales Value (NJOP), payment through collectors and designated places, and billing with bills and administrative actions in accordance with applicable laws. However, obstacles are still found, namely the lack of public understanding of the function and benefits of taxes and the ineffective application of legal sanctions